Psychological Capital as a Bridge between Role Clarity and Engagement: Empirical Insights from Village Officials in Waled - Ramadhani, Hendriansah; Gunawan, Asep; Febriyansyah, Hevy (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study investigates the effect of role clarity on employee engagement, with psychological capital as a mediating variable among village officials in Waled Subdistrict, Cirebon Regency. Using a quantitative approach with an explanatory design, the population was all village officials with a total of 136, the research sample used the census method. Data were collected through a 5-point Likert-scale questionnaire and analyzed using SPSS 22, including simple linear regression, partial t test, coefficient of determination (R2) and Sobel tests. Findings reveal that role clarity significantly influences employee engagement, both directly and indirectly through psychological capital. These results highlight the importance of structured job design and psychological development in optimizing human resource practices in the public sector.